1995
DOI: 10.1007/bf00186989
|View full text |Cite
|
Sign up to set email alerts
|

Number and size spectra of non-myelinated axons of human premolars

Abstract: The aim of this study was to determine the number and size of apical non-myelinated (C) axons of healthy human premolars. The material was derived from a large collection of specimens prepared for a previous quantitative investigation on the myelinated (A) axons of human premolars. A total of 16 teeth (six maxillary first and five each of mandibular first and second premolars), removed from adolescents for orthodontic reasons, were used. Root discs of about 0.6 mm thickness were prepared at about 2 mm cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The sensory neurons of the dental pulp have their cell bodies in the trigeminal ganglion. The long axons of the sensory neurons travel through the apical foramen in the neurovascular bundle and ascend to the radicular pulp . Each tooth is innervated by a multitude of trigeminal axons, which may have branched before entering the apical foramen and may innervate more than one tooth .…”
Section: Pulp Microenvironmentmentioning
confidence: 99%
“…The sensory neurons of the dental pulp have their cell bodies in the trigeminal ganglion. The long axons of the sensory neurons travel through the apical foramen in the neurovascular bundle and ascend to the radicular pulp . Each tooth is innervated by a multitude of trigeminal axons, which may have branched before entering the apical foramen and may innervate more than one tooth .…”
Section: Pulp Microenvironmentmentioning
confidence: 99%
“…For example, the conduction velocity of axons that innervate the dental pulp is higher in the extrapulpal than in the intrapulpal segment (5,6), and the proportion of myelinated to unmyelinated axons is higher in the inferior alveolar nerve than in the intrapulpal nerve (7,8). In addition, a large number of electron microscopic (EM) studies have reported that only 22%-45% of the intradental axons are myelinated in the radicular pulp of rats, cats, dogs, marmosets, and humans (9)(10)(11)(12)(13), whereas our previous study found that most axons innervating the rat dental pulp are myelinated at their site of origin in the trigeminal ganglion (TG) (14). Taken together, these results suggest that at least a large fraction of parent axons innervating the dental pulp lose their myelin between leaving the TG and entering the dental pulp.…”
mentioning
confidence: 99%
“…Studies by Nair et al . 4345 , using light and electron microscopy showed that healthy human premolars receive an average of 312 (+− 149) myelinated nerve fibers and 2000 non-myelinated axons (range 534–3912) at the juxta-apical pulp. Taken together these numbers are significantly higher than the values found in our work, and a possible explanation is the fact that the CLARITY/Light sheet microscopy method with the PGP9.5 antibody was not always able to distinguish fibers from larger fiber bundles.…”
Section: Resultsmentioning
confidence: 99%